Investigation of miR-21, miR-150, miR-155 Expression Levels in Chronic Myeloid Leukemia Patients - Hüseyin Avcılar; Hatice Altın; Sevil Şimşek; Leylagül Kaynar (Ahi Evran Medical Journal)
Purpose: In this study, the relationship between CML and the expression levels of miR-21, miR-150, and miR-155, which could be used in the follow-up of CML patients, was investigated.